2018
DOI: 10.1039/c7tb00646b
|View full text |Cite
|
Sign up to set email alerts
|

Development of tailored SPION-PNIPAM nanoparticles by ATRP for dually responsive doxorubicin delivery and MR imaging

Abstract: Smart theranostic SPION-NIPAM produced in small sizes show high drug loading capacity and pH/temperature-sensitive release which is also influenced by PNIPAM molecular weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…As reported in our previous article, SPION-PNIPAM with a crystal size of 7.2 � 2.7 nm, hydrodynamic size of 57 nm in water and an LCST at 38°C was synthesized. [40] Such small sizes are very critical to provide long-blood circulation time in the in vivo studies to prevent fast clearance of nanoparticles. This nanoparticle has about 84 wt% PNIPAM of a molecular weight (Mn) of 20.4 kDa (1.54 PDI).…”
Section: Etoposide Loaded Spion-pnipammentioning
confidence: 99%
“…As reported in our previous article, SPION-PNIPAM with a crystal size of 7.2 � 2.7 nm, hydrodynamic size of 57 nm in water and an LCST at 38°C was synthesized. [40] Such small sizes are very critical to provide long-blood circulation time in the in vivo studies to prevent fast clearance of nanoparticles. This nanoparticle has about 84 wt% PNIPAM of a molecular weight (Mn) of 20.4 kDa (1.54 PDI).…”
Section: Etoposide Loaded Spion-pnipammentioning
confidence: 99%
“…To unravel this difficulty, various strategies have been employed to prepare biodegradable or semi-degradable PNIPAM-based materials (135,160). In addition to polymeric materials, Aluminum oxide, and superparamagnetic Fe 2 O 3 nanoparticles have also been successfully modified with PNIPAM and reported for drug release applications (161,162). Protein release studies via PNIPAM and PEG-functionalized mesoporous silica nanoparticles reported recently (163).…”
Section: Thermo-responsive Polymersmentioning
confidence: 99%
“…One potentially fruitful organic-inorganic marriage is, for example, the integration of thermo-responsive polymers with paramagnetic/superparamagnetic metal hosting particle architectures. These polymers can mediate a significant change in hydration and solubility with changes in temperature [54][55][56], and have been applied to thermo-responsive drug release [57][58][59][60]. The integration of an associated high resolution imaging mode, such as MR, would also facilitate a direct imaging of treatment efficacy by magnetic hyperthermia.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%